Shockwave 3D - Wolf, Jason, 1970- (New Riders, 2002)
"Jason Wolf, a co-creator of Shockwave technology, gets you up to speed with this clearly written and practical book. Shockwave 3D gives you a software overview and then gets you quickly up to speed with accessible step-by-step instructions. Even traditional 3D designer new to Lingo programming will quickly learn how to export 3D scenes into Director, add interactive behavior, and publish content on the Internet. More advanced developers will appreciate the extensive Havok Lingo chapter and ray-casting examples, in addition to the numerous best practices."--BOOK JACKET.